Auditory verbal hallucinations (AVHs) and related psychotic phenomena in mood disorders: analysis of the 2010 Survey of High Impact Psychosis (SHIP) data. (30th September 2016) - Toh, Wei Lin; Castle, David J.; Thomas, Neil; Badcock, Johanna C.; Rossell, Susan L.
Abstract: Background: Auditory verbal hallucinations (AVHs) are known to occur in mood disorders, but there has been scant research in the area. This paper aimed to explore the presence of hallucinations, and AVHs in particular, across affective disorders (with non-affective disorders serving as clinical reference groups). Specific attention was given to i) running commentary, ii) voices conversing, and iii) negative voices. A secondary aim was to examine patterns of associated delusional themes. Method: Participants were 1550 Australians, aged 18–64 years, assigned to one of four groups on the basis of diagnosis: i) bipolar disorder (BD), ii) depressive psychosis (DP), iii) schizophrenia (SCZ), and iv) schizoaffective disorder (SAD). Relevant data collected from the 2010 Australian Survey of High Impact Psychosis (SHIP) was analysed. Results: Current prevalence of hallucinations was such that BD<DP; severity of hallucinations, and AVHs in particular, was in the order BD=DP<SAD=SCZ. These results were statistically significant. Negative voices, and concomitantly, persecutory delusions, were prominent across all clinical groups. Discussion: Future research should examine age of AVH onset as well as other forms of AVHs, whilst taking into account participants' specific mood states. Highlights: Current hallucinations were less prevalent in bipolar disorder than depressive psychosis. Voice-hearing experiences were less severe in affective versus non-affective psychoses. Negative voices and persecutory delusions were most prominent across all groups.